Diversity of Hypnea (Rhodophyta) in South Florida, with description of H. spiniformis sp. nov. - Nauer, Fabio; Freshwater, D. Wilson; Hatt, Danielle C.; Duran, Alain; Oliveira, Mariana C.; Campbell, Justin E.; Fujii, Mutue T.; Collado-Vides, Ligia (Phytotaxa, 2024)
The genus Hypnea is well known to be rich in cryptic species, with many new species being recognized recently based on molecular data. Therefore, we used mitochondrial (COI-5P) and plastid (rbcL) molecular markers, in addition to aspects of morphology, to investigate the diversity of Hypnea on the coast of South Florida. Molecular divergences and phylogenetic inferences indicated that four species were present: H. caraibica and H. cryptica, both new occurrences on the Florida coast; H. musciformis, already previously reported and H. spiniformis sp. nov. described in this work. Our data reinforce the importance of studies with an integrative taxonomy approach to delimit species and correctly identify them.